Short-Term Effects of Deliberate Subparaneural or Subepineural Injections With Saline Solution or Bupivacaine 0.75% in the Sciatic Nerve of Rabbits - Laredo, Francisco G.; Belda, Eliseo; Soler, Marta; Gil, Francisco; Murciano, José; Sánchez-Campillo, Joaquín; Agut, Amalia (Frontiers in Veterinary Science, 2020)
Background: Ultrasound (US)-guided techniques for peripheral nerve blockade has revealed that intraneural injections are relatively frequent and not necessarily associated with neurological deficits. Objectives: To evaluate the short-term effects of deliberate injections performed under direct vision in two different sites of the sciatic nerve (ScN). Material and Methods: Seventy-two New Zealand white rabbits randomly assigned to one of four experimental groups (n = 18) were employed. A fixed volume of 0.5 mL of saline solution (ES group) or bupivacaine 0.75% (EB group) was injected extrafascicularly inside the paraneurium of the ScN or intrafascicularly under the epineurium of the tibial nerve (TN) (IS and IB groups). Nerves were scanned by US and the cross sectional area (CSA) and relative echogenicity (RE) determined before injections, immediately after injections, and at 3 and 7 days. Additionally, nerve samples were obtained to conduct structural and ultrastructural histopathological studies. Proprioceptive, sensorial and motor function were clinically evaluated on a daily basis. Results: CSA values of the ScN determined by US immediately after injections, significantly increased when compared with pre-injection values in all groups (p < 0.05). RE values of the injected nerves decreased in relation to their pre-injection values in all groups (p < 0.05). CSA and RE values exhibited a trend to return to basal values at 3 and 7 days after injections. Apart from these findings, US scans of the ScN were unremarkable. Injected nerves showed mild signs of perineural inflammation but histopathological scores were not significantly different between groups (p > 0.05). The architecture of the ScN was preserved in all rabbits at 3 days, and in 31/32 rabbits at 7 days. A focal area of damaged nerve fibres with degeneration of the axons and myelin sheath affecting the TN was observed in one rabbit of the IB group. Nerve function was not clinically impaired in any case. Conclusion: Intrafascicular injections with saline solution and bupivacaine 0.75% produced mild signs of perineural inflammation without disruption of the nerve integrity in almost all cases. Changes in CSA and RE after injections were not associated with ScN deficits of clinical relevance.